2004
DOI: 10.1021/es0348391
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Thresholds as Indicators of Dehalorespiration in Constructed Treatment Wetlands

Abstract: Anaerobic degradation of cis-1,2-dichloroethene (cis-1,2-DCE) and 1,2-dichloroethane (1,2-DCA) was studied in microcosms derived from a laboratory-scale upflow treatment wetland system used to biodegrade chlorinated compounds present in groundwater from a Superfund site. Dechlorination kinetics of cis-1,2-DCE (0.94−1.57 d-1) and 1,2-DCA (0.15−0.71 d-1) were rapid, and degradation proceeded to completion with ethene or ethane as terminal dechlorination products. Hydrogen concentrations, measured simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…95, unpublished observations). Moreover, it has been suggested that reductive dehalogenating activity of "Dehalococcoides" can be triggered in anaerobic environments located in close spatial proximity to aerobic environments in wetland systems 73) .…”
Section: Biological Significance Of Reductive Dehalogenationmentioning
confidence: 99%
“…95, unpublished observations). Moreover, it has been suggested that reductive dehalogenating activity of "Dehalococcoides" can be triggered in anaerobic environments located in close spatial proximity to aerobic environments in wetland systems 73) .…”
Section: Biological Significance Of Reductive Dehalogenationmentioning
confidence: 99%
“…In addition, Dehalococcoides grow robustly in mixed cultures, likely due to currently undetermined growth factors from other community members (11,18,31,34,44). Though reductive dechlorination is an energetically favorable process under syntrophic conditions with low hydrogen partial pressures (19,57,58), other, less favorable metabolic reactions such as methanogenesis and acetogenesis often occur in these communities, especially when excess hydrogen or a donor fermented at high hydrogen partial pressures is available (19,20,24,38). Many methanogens depend on acetate and/or H 2 , which are both utilized by Dehalococcoides.…”
mentioning
confidence: 99%
“…This reaction is thermodynamically favorable, since it requires only one H 2 molecule for the removal of two chlorine substituents (8,16,26,40).…”
mentioning
confidence: 99%